Lightweight Block and Stream Cipher Algorithm: A Review - Suaad Ali Abead; Nada Hussein M. Ali (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
Most of the Internet of Things (IoT), cell phones, and Radio Frequency Identification (RFID) applications need high speed in the execution and processing of data. this is done by reducing, system energy consumption, latency, throughput, and processing time. Thus, it will affect against security of such devices and may be attacked by malicious programs. Lightweight cryptographic algorithms are one of the most ideal methods Securing these IoT applications. Cryptography obfuscates and removes the ability to capture all key information patterns ensures that all data transfers occur Safe, accurate, verified, legal and undeniable. Fortunately, various lightweight encryption algorithms could be used to increase defense against various attacks to preserve the privacy and integrity of such applications. In this study, an overview of lightweight encryption algorithms, and methods, in addition, a modern technique for these algorithms also will be discussed. Besides, a survey for the algorithm that would use minimal power, require less time, and provide acceptable security to low-end IoT devices also introduced, Evaluating the results includes an evaluation of the algorithms reviewed and what was concluded from them. Through the review, we concluded that the best algorithms depend on the type of application used. For example, Lightweight block ciphers are one of the advanced ways to get around security flaws.